Dale una Mano a los Bosques: Guia de Accion Juvenil - Janice Easton; Martha C. Monroe; Alison Bowers; Gabriella Scollo (EDIS)
Revised! Circular 1269-S, a 109-page illustrated guide by Janice Easton, Martha C. Monroe, and Alison W. Bowers, is the Spanish language version of Circular 1269, Give Forests a Hand Youth Action Guide, translated by Gabriella Scollo. Published by the UF School of Forest Resources and Conservation, September 2006.